2020
DOI: 10.1155/2020/5737289
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA 00312 Attenuates Cell Proliferation and Invasion and Promotes Apoptosis in Renal Cell Carcinoma via miR-34a-5p/ASS1 Axis

Abstract: Background. Previous studies have demonstrated that lncRNAs play functional roles in regulating cancer cell proliferation, invasion, and apoptosis. Recent studies confirmed that lncRNA 00312 has important biological functions in lung and colorectal cancer. However, the role of lncRNA 00312 in renal cell carcinoma (RCC) remains unclear. Our aim was to explore the function of lncRNA 00312 in RCC and its potential molecular mechanism. Methods. RCC cell lines A498 and ACHN were used as in vitro models in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In recent decades, many studies have found the critical function of lncRNAs in many types of human cancer, including RCC [ 11 , 26 , 27 ]. This evidence is of benefit to clarify the mechanistic basis of RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, many studies have found the critical function of lncRNAs in many types of human cancer, including RCC [ 11 , 26 , 27 ]. This evidence is of benefit to clarify the mechanistic basis of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, enhanced lncRNA ARSR expression was shown in RCC‐initiating cells, related with dismal survival, and contributed to the sunitinib resistance in RCC patients [ 10 ]. Results from Zeng et al showed that lncRNA 00312 could prohibit RCC cell proliferation and migration and boost apoptosis in vitro by repressing miR-34a-5p and enhancing expression of ASS1 [ 11 ]. Some lncRNAs named small nucleolar RNA host genes (SNHGs), which can encode small nucleolar RNAs (snoRNAs) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] LncRNAs exert oncogenic or suppressive functions in various human cancers, including RCC. [8][9][10] LncRNA small nuclear RNA host gene 17 (SNHG17) is located on 20q11. 23, with a 1,186 nt in length.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lncRNA TPTEP1 could inhibit the non-small cell lung cancer (NSCLC) cells to proliferate through abating miR-328-5p expression (Cao et al, 2020). In addition, in renal cell carcinoma, lncRNA00312 attenuated cell proliferation and migration obviously (Zeng et al, 2020). However, the study about lncRNA functioned in HSCR is rarely reported.…”
Section: Introductionmentioning
confidence: 99%